Specimen banking: saving for the future - Gunter, Elaine (Henry Stewart Talks, 2007)
The rationale for specimen banking, Recommended practices, Genetic analyses prior to banking nucleic acids or tissues, Long-term storage of samples, Access to the resource, Analysis of samples, Choice of markers, Types and testing of markers, Major banking programs
Reviewed at 2018/06/01